Evaluasi Implementasi Risk Based Internal Audit (Studi Kasus pada PT ABC) - Aulia, Nabilah; Julian, Lufti (Politeknik Ganesha Medan, 2024)
This research was conducted to analyze the effectiveness of the implementation of Risk Based Internal Audit (RBIA) at PT ABC by using the framework from David Griffith in 2020 related to the implementation of RBIA and the Chartered Institute of Internal Auditors in 2014 in evaluating risk maturity as part of RBIA implementation. This research is a case study with a descriptive qualitative approach using interviews and document analysis to explore experiences and in-depth understanding. The object of research is PT ABC, which is a private manufacturing company engaged in the manufacturing industry. In the past, the company has experienced poor financial conditions. Therefore, PT ABC tries to carry out effective supervision, one of which is carried out through the internal audit division. However, in practice, management's commitment to managing risk has not been fully reflected in company practice. PT ABC management does not have a policy as a form of tone of the top commitment in implementing risk management. The results of the study can be concluded that PT ABC has not been able to implement RBIA comprehensively because the results of the risk maturity assessment carried out are still at level risk naïve. Improvements are needed to increase the level of risk maturity to implement RBIA comprehensively or when the risk assessment reaches level risk defined. This research provides recommendations for a roadmap that can be implemented by PT ABC to increase risk maturity so that RBIA can be implemented comprehensively in the future.